Advancing nature-based solutions through enhanced soil health monitoring in the United Kingdom - Giuliani, LM; Warner, E; Campbell, GA; Lynch, J; Smith, AC; Smith, P (Wiley, 2024)
Soil health is a critical component of Nature-based Solutions (NbS), underpinning ecosystem multifunctionality and resilience by supporting biodiversity, improving carbon sequestration and storage, regulating water flow, and enhancing plant productivity. For this reason, NbS often aim to protect soil health and restore degraded soil. Robust monitoring of soil health is needed to adaptively manage NbS projects, identify best practices and minimise trade-offs between goals, but soil assessment is often underrepresented in NbS monitoring programmes. This paper examines challenges and opportunities in selecting suitable soil health metrics. We find that standardisation can facilitate widespread monitoring of soil health, with benefits for stakeholders and user groups. However, standardisation brings key challenges including the complexity and local variability of soil systems and the diverse priorities, skills and resources of stakeholders. To address this, we propose a flexible, interdisciplinary approach combining soil science, ecology and socio-economic insights. We introduce an interactive tool to help users select suitable soil and biodiversity metrics which are context and scalespecific, and suggest avenues for future research. We conclude that integrating soil health into NbS through new and improved monitoring approaches, newly available datasets, supportive policies, and stakeholder collaboration can enhance the resilience and effectiveness of NbS, contributing significantly to global sustainability goals.